NILAI-NILAI MORAL DALAM PEMBELAJARAN ANAK USIA DINI DENGAN GAME EDUKASI CULLEN ABC?óÔé¼Ôäós BAGI GURU-GURU PAUD DI KECAMATAN TEMBALANG SEMARANG - Subur Laksmono Wardoyo; Ghufron Abdullah; Ririn Ambarini; Sari Kusumaningrum (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2014)
Abstract Science and technology?é?á transferred to the?é?á teachers of early childhood education in?é?á Tembalang Semarang?é?á are the training how to apply the moral values ?óÔé¼ÔÇ??óÔé¼ÔÇ?in the learning for early childhood and?é?á the?é?á use of software Cullen ABC 's as teaching aids for developing creativity and intellectual power of early childhood where the material delivered in training is , " Bringing Books in the Life of Early Childhood : Teaching Character Education Through Children's Literature " , " Moral Values ?óÔé¼ÔÇ??óÔé¼ÔÇ?of Early Childhood Education and Cullen ABC 's " , "the?é?á Use of story For Development of Moral Education for Early Childhood " , and " ABC 's Cullen as Educational Games and Teaching Aids " . With the IBM moral values ?óÔé¼ÔÇ??óÔé¼ÔÇ?in the learning of Cullen ABC 's as an educational game as well teaching aids it is hoped that the workshop will contribute to teachers early childhood to develop more creative ideas in teaching so that the learning environment will be more enjoyable while also fostering moral values ?óÔé¼ÔÇ??óÔé¼ÔÇ?since the early life . Keywords: Moral Values ?óÔé¼ÔÇ??óÔé¼ÔÇ?, Early Childhood Education , Cullen ABC 's .